Catalytic intramolecular aminoarylation of unactivated alkenes with aryl sulfonamides. Issue 23 (26th May 2022) - Noten, Efrey A.; McAtee, Rory C.; Stephenson, Corey R. J.
Abstract : A photochemical assembly of cyclic arylethylamines occurs by cascade radical annulation and desulfonylative rearrangement in N -acyl sulfonamides. This aminoarylation is made possible through judicious design intended to thwart undesired reactivity. Abstract : Arylethylamines are abundant motifs in myriad natural products and pharmaceuticals, so efficient methods to synthesize them are valuable in drug discovery. In this work, we disclose an intramolecular alkene aminoarylation cascade that exploits the electrophilicity of a nitrogen-centered radical to form a C–N bond, then repurposes the nitrogen atom's sulfonyl activating group as a traceless linker to form a subsequent C–C bond. This photoredox catalysis protocol enables the preparation of densely substituted arylethylamines from commercially abundant aryl sulfonamides and unactivated alkenes under mild conditions. Reaction optimization, scope, mechanism, and synthetic applications are discussed.